A Jelenkor a nemzeti identitás és a polgári átalakulás szolgálatában az 1830-as években - Döbör, András (Közép-Európai Közlemények, 2012)
In my presentation, I would like to introduce the investigation of a news-sheet from the Reform Era, namely the Jelenkor, from two different viewpoints. First of all, it appears as a medium in the enrichment and development of our national language, the Hungarian education, science and culture. On the other hand, it was an openly ongoing discussion which had a significant role in the foundation of the national identity and the performance of earl István Széchenyi, who established and cultivated the Hungarian literacy.